2005
DOI: 10.1073/pnas.0502393102
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-specific IFN-γ/IL-2-secreting CD8 T cells support CD4-independent proliferation of HIV-1-specific CD8 T cells

Abstract: Functional and phenotypic characterization of virus-specific CD8 T cells against cytomegalovirus, Epstein-Barr virus, influenza (flu), and HIV-1 were performed on the basis of the ability of CD8 T cells to secrete IFN-γ and IL-2, to proliferate, and to express CD45RA and CCR7. Two functional distinct populations of CD8 T cells were identified: ( i ) dual IFN-γ/IL-2-secreting cells and ( ii ) single IFN-γ-secreting cells. Virus-specific IFN-γ/IL-2-secreting CD8 T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
287
4
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 273 publications
(319 citation statements)
references
References 29 publications
24
287
4
2
Order By: Relevance
“…These results show that HCV-specific T cells in HCV monoinfection have a polyfunctional profile similar to that of virusspecific CD4 1 and CD8 1 T cells found in normally controlled infections with low or undetectable persistent viral load such as CMV, EBV, HSV, influenza and HIV-1-infected subjects with nonprogressive disease [22,25,28]. In contrast, HCV-specific T-cell responses in HIV/HCV co-infected individuals and liver transplant recipients have the ''only effector'' profile and resemble those detected in uncontrolled viral infections such as untreated viremic HIV-1 infection [22,25]. The reduction in IL-2-producing CD4 1 and CD8 1 T cells can directly explain the impaired capacity of these cells to proliferate [25].…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…These results show that HCV-specific T cells in HCV monoinfection have a polyfunctional profile similar to that of virusspecific CD4 1 and CD8 1 T cells found in normally controlled infections with low or undetectable persistent viral load such as CMV, EBV, HSV, influenza and HIV-1-infected subjects with nonprogressive disease [22,25,28]. In contrast, HCV-specific T-cell responses in HIV/HCV co-infected individuals and liver transplant recipients have the ''only effector'' profile and resemble those detected in uncontrolled viral infections such as untreated viremic HIV-1 infection [22,25]. The reduction in IL-2-producing CD4 1 and CD8 1 T cells can directly explain the impaired capacity of these cells to proliferate [25].…”
Section: Discussionmentioning
confidence: 54%
“…Recent studies have indeed shown that the proliferation capacity of virus-specific CD4 and CD8 T cells is dependent upon the presence of IL-2-producing cells and that the presence of virus-specific proliferating cells is associated with control of virus replication [22,24,25]. Both CD4 1 ( Fig.…”
Section: Impaired Proliferation Of Hcv-specific T Cells In Patients Wmentioning
confidence: 91%
See 3 more Smart Citations